Cancer health literacy in Kenya - A scoping review on evidence, concept and a situational analysis of interventions - Harsch, Stefanie; Weber, Lea S.; Kassaman, Dinah; Kailemia, Peter N.; Oria, Victor O. (Frontiers in Public Health, 2025)
BackgroundIn light of the rising incidences of cancer in Kenya, there is an urgent need to evaluate and strengthen cancer health literacy (CHL). Nevertheless, no review has been undertaken to synthesise the empirical evidence on CHL in Kenya. This study aims to review the evidence, explore the use of the concept CHL and, assess the situation of HL interventions.MethodA comprehensive scoping review was conducted to explore the evidence on CHL in Kenya. The review included a thorough concept analysis, based on the work of Sorensen et al. and a situational analysis, employing the precede–proceed model of Green and Kreuter. Nine international scientific databases (PubMed, Web of Science, CINAHL, APA PsycINFO, OpenDissertation, ERIC, Cochrane Library, African Journals Online, and African Index Medicus) were searched to identify articles on cancer health literacy-related concepts in Kenya since 2010. Two researchers screened the titles and abstracts and analysed the full texts based on the eligibility criteria. Data was extracted using a deductively developed coding scheme.ResultsA total of 727 articles were identified, of which 110 deemed eligible for analysis. The studies presented findings on the geographical distribution, cancer type, phase of the cancer care continuum, target group, cancer-related aspects, and intervention's influencing factors. Most studies concentrated on early detection and assessed barriers and facilitators. A mere 31 studies reported on treatment. There is a paucity of knowledge regarding educational interventions for cancer patients and their effectiveness. The concept of CHL was primarily concerned with possessing knowledge and information, with relatively little attention devoted to the processes of using them, specifically their appraisal and application. Various situational aspects of interventions were identified.ConclusionFurther research is required to develop and implement promising interventions for the general public and cancer patients, enabling them to utilise information more effectively. Interventions that are decentralised, digital, and involve cancer patients and survivors are recommended to meet the needs of the growing numbers of cancer patients and their families. The findings can inform the development of promising CHL interventions and mitigate their barriers in Kenya and beyond.